Personal involvement is related to increased search motivation and associated with activity in left BA44—a pilot study - Schaefer, Michael; Rumpel, Franziska; Sadrieh, Abdolkarim; Reimann, Martin; Denke, Claudia (Frontiers in Human Neuroscience, 2015)
Numerous studies explore consumer perception of brands in a more or less passive way. This may still be representative for many situations or decisions we make each day. Nevertheless, sometimes we often actively search for and use information to make informed and reasoned choices, thus implying a rational and thinking consumer. Researchers suggested describing this distinction as low relative to high involvement consumer behavior. Although the involvement concept has been widely used to explain consumer behavior, behavioral and neural correlates of this concept are poorly understood. The current study aims to describe a behavioral measure that is associated with high involvement, the length of search behavior. A second aim of this study was to explore brain activations associated with involvement by employing functional magnetic resonance imaging (fMRI). We presented participants information cues for different products and told them that they had to answer questions with respect to these products at the end of the experiment. Participants were free to stop the information search if they think they gathered enough information or to continue with collecting information. Behavioral results confirmed our hypothesis of a relationship between searching behavior and personal involvement by demonstrating that the length of search correlated significantly with the degree of personal involvement of the participants. FMRI data revealed that personal involvement was associated with activation in BA44. Since this brain region is known to be involved in semantic memory, the results of this pilot study suggest that high involvement consumer behavior may be linked to cognitive load and attention towards a product.